2008
DOI: 10.3892/mmr.1.4.525
|View full text |Cite
|
Sign up to set email alerts
|

Significant association of XRCC4 single nucleotide polymorphisms with prostate cancer susceptibility in Taiwanese males

Abstract: Abstract. The DNA repair gene X-ray cross-complementing group 4 (XRCC4), a member of the non-homologous endjoining (NHEJ) repair system, plays a major role in the repair of the double-strand breaks of the DNA sequence. This gene is critical to the maintenance of overall genome stability, and is also thought to play a key role in human carcinogenesis. In this case-control study, several novel polymorphic variants of XRCC4, including C-1622T (rs7727691), G-1394T (rs6869366), C-571T (rs2075686) and intron3 DIP (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 14 publications
1
53
2
Order By: Relevance
“…Previous studies indicated that polymorphism of CSB rs2228526 was associated with susceptibility and prognosis of various cancer, such as skin cancer, bladder cancer and bone malignant tumor as well as glioblastoma (Chang et al, 2009;Grunda et al, 2010;Wheless et al, 2012;Sun et al, 2013). Another experimental study indicated that chronic exposure to arsenic causes DNA damage and increased cell survival that may ultimately result in neoplastic transformation of human prostate epithelial cells (Singh et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that polymorphism of CSB rs2228526 was associated with susceptibility and prognosis of various cancer, such as skin cancer, bladder cancer and bone malignant tumor as well as glioblastoma (Chang et al, 2009;Grunda et al, 2010;Wheless et al, 2012;Sun et al, 2013). Another experimental study indicated that chronic exposure to arsenic causes DNA damage and increased cell survival that may ultimately result in neoplastic transformation of human prostate epithelial cells (Singh et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies are still required to confirm this predicted biological significance. By reviewing the currently available literatures on ERCC6 polymorphisms, we noted that associations of another frequently-reported SNP rs2228528 with different cancers have been described including oral cancer (Chiu et al, 2008), lung cancer (Ma et al, 2009) and bladder cancer (Chang et al, 2009). The rs2228528 polymorphism located in the exon 5 of ERCC6 gene is in highly linkage disequilibrium with the currently-investigated SNP rs1917799 (r 2 =0.95, derived from CHB genotype data of HapMap Project).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, disruption of this gene was related to the development of age-related macular degeneration (Tuo et al, 2006). Quite recently, genetic variations of ERCC6 have been linked to the susceptibility to various cancers, including lung cancer (Lin et al, 2008;Ma et al, 2009), breast cancer (Mechanic et al, 2006;Rajaraman et al, 2008), prostate cancer (Hooker et al, 2008), bladder cancer (Chen et al, 2007;Chang et al, 2009) and colorectal cancer Huang et al, 2006). However, the relation of ERCC6 polymorphism with gastric cancer risk is still unclear, which deserves to be further clarified.…”
Section: Research Articlementioning
confidence: 99%
“…So, risky genotypes have an effect on cancer susceptibility [20]. Wu et al [32] reported 12 missense single nucleotide polymorphisms in the EXO1 gene including K589E in exon11 [21][22][23][24][25][26][27][28][29][30][31][32]. An exonic SNP doesn't necessarily cause a dysfunctional protein.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic polymorphisms in DNA repair genes such as EXO1 are thought to modulate DNA repair capacity and consequently are suggested to be associated with colorectal cancer [22]. Singlenucleotide polymorphism (SNP) is a DNA sequence variation and has a great potential application to determine association with susceptibility to several cancers such as oral, breast, prostate, gastric and colorectal cancer [23][24][25][26][27][28][29][30][31]. These indicate that substitution in these SNPs may effect on genes' functions or expression levels.…”
Section: Introductionmentioning
confidence: 99%